Genome evolution in Arabideae was marked by frequent centromere repositioning - Mandáková, Terezie; Hlouskova, Petra; Koch, Marcus; Lysák, Martin A. (The plant cell, 2020)
Frequent centromere repositioning is the key mechanism differentiating homoeologous chromosomes in Arabideae genomes in the absence of gross chromosomal rearrangements. Centromere position may change despite conserved chromosomal collinearity. Centromere repositioning and evolutionary new centromeres (ENCs) were frequently encountered during vertebrate genome evolution but only rarely observed in plants. The largest crucifer tribe, Arabideae (similar to 550 species; Brassicaceae, the mustard family), diversified into several well-defined subclades in the virtual absence of chromosome number variation. Bacterial artificial chromosome-based comparative chromosome painting uncovered a constancy of genome structures among 10 analyzed genomes representing seven Arabideae subclades classified as four genera: Arabis, Aubrieta, Draba, and Pseudoturritis. Interestingly, the intra-tribal diversification was marked by a high frequency of ENCs on five of the eight homoeologous chromosomes in the crown-group genera, but not in the most ancestral Pseudoturritis genome. From the 32 documented ENCs, at least 26 originated independently, including 4 ENCs recurrently formed at the same position in not closely related species. While chromosomal localization of ENCs does not reflect the phylogenetic position of the Arabideae subclades, centromere seeding was usually confined to long chromosome arms, transforming acrocentric chromosomes to (sub)metacentric chromosomes. Centromere repositioning is proposed as the key mechanism differentiating overall conserved homoeologous chromosomes across the crown-group Arabideae subclades. The evolutionary significance of centromere repositioning is discussed in the context of possible adaptive effects on recombination and epigenetic regulation of gene expression.